Novel SiO2-C composite adsorptive material - Scian, Alberto Néstor (2001)
The present work is about the development of a Novel Composite that has several properties in only one material. This material is composed by a silica network with a sharpened pore size distribution - diameter near 1000 Å - intercrossed with another carbon network that has carbonaceous microdomains of high activity. The first network facilitates the entrance of big molecules to the interior of the material grains so they quickly reach the active sites of the carbonous network, minimizing the diffusional resistance observed when high performance activated carbons are used in adsorption processes or catalytic applications. These two intercrossed structures are self-supporting and independent among them, so one from the other can be isolated without losing the original shape and volume of the starting composite, then, their possible uses may be multiplied. The Novel Composite is stable with respect to other support or adsorbent materials due to its high obtention temperature (1550 °C). The obtention methods of the composite and its isolated structures are described. The material was characterized by different techniques (XRD, IR, Loss on ignition, pore size distribution, specific surface area, adsorption desorption isotherms, methylene blue adsorption and SEM).